Strength Properties of Alkaline Activated Phosphoric Acid Stabilized Laterite - Adekemi Loretta AYODELE; Abideen Morakinyo Akinniyi; Adeoluwa Peter Gbolade; Adeyemi Timilehin Adetokunbo (Civil Engineering Dimension, 2022)
This study investigated the effect of alkaline activation on the properties of Phosphoric Acid (PA) stabilized laterite. Maximum Dry Density (MDD), Optimum Moisture Content (OMC), California Bearing Ratio (CBR) and Unconfined Compressive Strength (UCS) of the laterite were determined to ascertain its suitability as a construction material. Laterite samples were stabilized with 1M and 2M PA at 5, 10 and 15%, respectively, by weight of dry soil. Some PA stabilized laterite were further mixed with an alkaline activator. All the stabilized laterites were moist cured for up to 14 days. The results show that the laterite was unsuitable as a road construction material in its natural state. The CBR of PA stabilized laterite improved with about 25%, while that with alkaline activation showed more improvement of up to 145%. The UCS of PA stabilized soil and that with alkaline activation increased with about 250% improvement. In conclusion, alkaline activation of phosphoric acid stabilized laterite soil for road construction has a great promise.